Behaviour Of Selected Criteria Air Pollutants During High Particulate Event - Leong, Weng Woh (Universiti Sains Malaysia, 2017)
Nitrogen Dioxide (NO2), Ground Level Ozone (O3), and Particulate Matter with size less than 10 micron (PM10) are air pollutants measured in Malaysia Ambient Air Quality Guideline since 1989. Focus of this research is the interaction between each air pollutant as well as the effects of daytime (DT), nighttime (NT), 4 monsoon seasons and high particulate events that occurred in one year. Descriptive analysis and diurnal plot is produced by using Microsoft Excel 2016. From the result of the analysis, seasonal variation shows least effect on the annual trends for each pollutant. Even the effect on each pollutant is less significant, the effect to monthly mean value shows that HPE have highest mean value PM10 concentration of 116.16 μg/m3 while April-May inter-monsoon have the lowest concentration of all three air quality parameters with PM10 (24.09 μg/m3), O3 (5.35 ppb and 8.83 ppb) and NO2 (6.61 ppb and 7.93 ppb) while September-October inter-monsoon has higher mean concentration than April-Mei (PM10 with 53.20 μg/m3; O3 with 22.33 ppb dan NO2 with 8.29 ppb). DT and NT provide the information whereby O3 and NO2 are highly dependent on the daily human activities and sunlight as these two pollutants have drastically difference between DT and NT. Besides, study also shown that the mean concentration of PM10 in Taiping monitoring station has positive correlation coefficient towards O3 which dedicate that the increase of PM10 will result in increase of O3. Dissertation also include analysis of 5 different monitoring station, CA04, CA07, CA22, CA25, and CA38 to study the influence of high particulate event on concentration of PM10, O3, NO, and NO2. From the results of correlation coefficient, the R value for these air pollutants during HPE is lower than during non-HPE.